2016
DOI: 10.1021/acs.est.6b00032
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of Bisphenols and Their Association with Biomarkers of Oxidative Stress in People Living Near E-Waste Recycling Facilities in China

Abstract: In this study, concentrations of bisphenol A (BPA) and seven other bisphenols (BPs) were measured in urine samples collected from people living in and around e-waste dismantling facilities, and in matched reference population from rural and urban areas in China. BPA, bisphenol S (BPS), and bisphenol F (BPF) were frequently detected (detection frequencies: > 90%) in urine samples collected from individuals who live near e-waste facilities, with geometric mean (GM) concentrations of 2.99 (or 3.75), 0.361 (or 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(78 citation statements)
references
References 54 publications
11
67
0
Order By: Relevance
“… 32 Median BPF levels of 0.365 μg/L (<LOD to 8.68 μg/L; N = 116) were observed in a Chinese population living near an E-waste-dismantling area. 59 These levels are comparable to the levels observed in the adult NHANES 2013–2014 population in this study ( Table 1 ). Median BPS levels in this study (0.37 μg/L) were higher than BPS levels (median 0.191 μg/L, <LOD to 21.0 μg/L; N = 315) observed in urine samples collected from 2010 to 2011 in several Asian countries, including China, India, Korea, Kuwait, Malaysia, and Vietnam.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“… 32 Median BPF levels of 0.365 μg/L (<LOD to 8.68 μg/L; N = 116) were observed in a Chinese population living near an E-waste-dismantling area. 59 These levels are comparable to the levels observed in the adult NHANES 2013–2014 population in this study ( Table 1 ). Median BPS levels in this study (0.37 μg/L) were higher than BPS levels (median 0.191 μg/L, <LOD to 21.0 μg/L; N = 315) observed in urine samples collected from 2010 to 2011 in several Asian countries, including China, India, Korea, Kuwait, Malaysia, and Vietnam.…”
Section: Resultssupporting
confidence: 86%
“… 32 Levels of 2.99 μg/L (0.233–27.6 μg/L; N = 116) were reported for a more highly exposed population living near an E-waste-dismantling area in China. 59 …”
Section: Resultsmentioning
confidence: 99%
“…This suggests that a ‘cocktail’ of chemicals from the environment—which is realistic in our current daily environment—increases the risk of aberrant methylation in male germ cells. Interestingly, exposures to EDCs have also been shown to alter fatty acid composition and decrease anti-oxidant enzyme level in the testis [ 67 ], inducing oxidative stress [ 68 ] and ultimately affecting spermatogenesis [ 69 ]. Occupational exposures to bisphenol A was also shown to impact global sperm DNA methylation in humans [ 70 ].…”
Section: Why Study Exposure To Environmental Toxins In Future Fathersmentioning
confidence: 99%
“…In rodents, BPS decreased body weight [ 14 ], induced oxidative stress and morphological alterations in the male reproductive system [ 15 ], and affected transcription of genes related to the dopamine-serotonin systems [ 16 ]. In zebrafish, BPS altered the embryonic nervous and endocrine systems [ 17 ], and induced developmental and reproductive abnormalities [ 18 ]. In vitro studies have found that BPS induces morphological and biochemical alterations in different types of human blood cells, alters the meiotic cycle of porcine oocytes, and has weak estrogenic activity [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%